Analisis Implementasi Kurikulum 2013 terhadap Pembelajaran Kimia di SMA Negeri se-Kabupaten Wajo - Dalle, Firda Anwar; Muharram, Muharram; Hasri, Hasri (Program Pasca Sarjana UNM, 2021)
This study aims to find out 1) planning, 2) implementation, 3) assessment of Chemistry learning in the 2013 Curriculum, 4) Obstacles in implementing Chemistry learning in the 2013 Curriculum. This type of research is classified as evaluation research. Sources of data were obtained from all Chemistry teachers in Senior High School of Wajo who had implemented the 2013 Curriculum, the research data included planning, implementing, evaluating Chemistry learning. Data collection techniques using checklist sheets, interviews, observations, questionnaires, and documentation. The results of this study indicate that the Chemistry Learning Planning Aspects of the 2013 Curriculum in Senior High School of Wajo in the even semester of the academic year 2019/2020 reached 91% included in the very complete category, the Learning Implementation Aspect reached 87% included in the good category, and in the Aspect Chemistry Learning Assessment reached 73% included in the quite good category. The obstacles that have not been maximally implemented in the implementation of the 2013 curriculum are on the use of a scientific approach, the use of the 2013 curriculum-based learning model, as well as on the assessment of learning in the 2013 curriculum.